The Impact of Accessible Cervical Cancer Screening in Peru—The Día del Mercado Project. Issue 3 (July 2015) - Ferris, Daron G.; Shapiro, John; Fowler, Christopher; Cutler, Carolyn; Waller, Jennifer; Guevara Condorhuaman, Wendy Shulay
Abstract : Objective: The purpose of this study was to determine the potential impact of accessible secondary cervical cancer prevention efforts in indigenous Peruvian women living in the rural Andes Mountain region of Peru. Methods: Peruvian women presenting for a Pap test or visiting a local marketplace, clinic, or public facility were asked to complete a questionnaire that assessed their response to the rural Pap screening program. We identified the following: 1) barriers to care, 2) patient knowledge of cervical cancer and Pap tests, and 3) perceptions of and reactions to the market clinic model. Chi-square or Fisher exact tests, t tests and 1-way ANOVA were used to examine differences between locations. Results: Of 4, 560 women enrolled, those examined in tents indicated it was easier to get a Pap test (98.7%, P = 0.001) compared with women seen in buildings (96.8%) or CerviCusco (98.0%), and they felt it was more important to have a Pap test close to their home more often (99.3%) than those seen at CerviCusco (97.8%) or buildings (98.8%). Women examined in tents felt the market was a good place to have a Pap test more often (67.0%, P < 0.001) than women who went to buildings (46.0%) or CerviCusco (29.2%). Conclusions: Many poor indigenous women living in isolated regions are unable to travel to distant health-care facilities. Using a novel mobile clinic model, the "Dia del Mercado Project" successfully reduced barriers to cervical cancer screening by using local marketplaces. Abstract : Precis: The "Día del Mercado Project" used a novel mobile clinic model in which health-care professionals reduced barriers to cervical cancer screening by using local marketplaces.